العلاقة بين ممارسة الأنشطة الترويحية وإشباع الحاجات النفسية والسلوك العدواني لدى تلاميذ المرحلة الابتدائية (Comprehensive Journal of Science, 2025)
This study investigates the impact of recreational activities on fulfilling psychological needs and reducing aggressive behaviour among primary school students by comparing participants and non-participants. Recreational activities are essential for children’s psychological and social development, particularly in the primary stage, which forms the foundation for behavioural, social, and emotional skills. A descriptive-analytical comparative approach was employed. The study population included primary school students, with a random sample of participants and non-participants selected from various schools to ensure representation. Valid and reliable measurement tools assessed psychological needs fulfilment and aggressive behaviour. Results indicated that students engaging in recreational activities exhibited higher levels of psychological needs satisfaction and lower levels of aggressive behaviour compared to non-participants. Strong positive correlations were found between recreational activity participation and psychological needs fulfilment, while strong negative correlations were observed between participation and aggressive behaviour. Additionally, a negative correlation existed between psychological needs fulfilment and aggressive behaviour, These findings highlight the significant role of recreational activities in enhancing children’s psychological well-being, reducing aggression, and developing social and emotional skills, thereby promoting holistic growth. The study recommends integrating recreational activities into school curricula, training teachers to design and implement such activities effectively, and fostering collaboration between schools and families to encourage active participation.
Keywords: Recreational activities – Psychological needs fulfilment – Aggressive behaviour – Primary school students – Children’s psychological well-being